Peptide (Lys–Leu) and amino acids (Lys and Leu) supplementations improve physiological activity and fermentation performance of brewer's yeast during very high‐gravity (VHG) wort fermentation. (16th January 2018) - Yang, Huirong; Zong, Xuyan; Cui, Chun; Mu, Lixia; Zhao, Haifeng
Abstract: Lys and Leu were generally considered as the key amino acids for brewer's yeast during beer brewing. In the present study, peptide Lys–Leu and a free amino acid (FAA) mixture of Lys and Leu (Lys + Leu) were supplemented in 24 °P wort to examine their effects on physiological activity and fermentation performance of brewer's yeast during very high‐gravity (VHG) wort fermentation. Results showed that although both peptide Lys–Leu and their FAA mixture supplementations could increase the growth and viability, intracellular trehalose and glycerol content, wort fermentability, and ethanol content for brewer's yeast during VHG wort fermentation, and peptide was better than their FAA mixture at promoting growth and fermentation for brewer's yeast when the same dose was kept. Moreover, peptide Lys–Leu supplementation significantly increased the assimilation of Asp, but decreased the assimilation of Gly, Ala, Val, (Cys)2, Ile, Leu, Tyr, Phe, Lys, Arg, and Pro. However, the FAA mixture supplementation only promoted the assimilation of Lys and Leu, while reduced the absorption of total amino acids to a greater extent. Thus, the peptide Lys–Leu was more effective than their FAA mixture on the improvement of physiological activity, fermentation performance, and nitrogen metabolism of brewer's yeast during VHG wort fermentation.